Reflooding the coupled human and natural system of the Waza-Logone Floodplain, Cameroon - Moritz, Mark; Hunter, Chelsea E.; Scholte, Paul (Frontiers in Conservation Science, 2024)
The rewilding framework is used to guide the restoration of ecological processes in natural systems, but the framework can also be used in the restoration of social and ecological processes in coupled human and natural systems. We use the case of the largescale reflooding of the Waza-Logone Floodplain in Cameroon three decades ago as an example of rewilding a coupled human and natural system. Drawing on studies that have been conducted of the Logone Floodplain and Waza National Park over the last five decades, we discuss the reflooding efforts, review the long-term impact of the reflooding, and reflect on the assumptions of the reflooding effort. Our review shows that restoring the hydrological and ecological processes benefitted human populations but was not sufficient for supporting wildlife; and, political dynamics impact ecological processes and must be considered for rewilding to succeed.